7 Changes in emotion processing associated with brief augmented psychodynamic interpersonal therapy for functional neurological symptoms. Issue 8 (13th July 2017) - Williams, Isobel Anne; Howlett, Stephanie; Levita, Liat; Reuber, Markus
Abstract : Objective: The putative links between abnormal emotion processing and Functional Neurological Symptoms (FNS) suggest that this patient group might benefit from a psychotherapeutic intervention targeting the perception, naming, tolerance, and expression of emotions. Brief Augmented Psychodynamic Interpersonal Therapy, an intervention designed to address emotion processing difficulties, has previously been associated with improvements in health-related quality of life and psychological distress in patients with FNS. The objective of this study was therefore to determine whether improvements in clinical symptomology following Brief Augmented Psychodynamic Interpersonal Therapy, were associated with improvements in emotion processing. A second exploratory objective was to see if there were any identifying characteristics of patients who made a clinically significant improvement in emotion processing. Method: battery of self-report questionnaires was administered to patients with FNS (n=44), prior to and following a course of Brief Augmented Psychodynamic Interpersonal Therapy. Emotion Processing was measured using the Emotion Processing Scale (EPS-25). The Short Form 36 (SF-36), Clinical Outcomes in Routine Evaluations (CORE 10), Patient Health Questionnaire (PHQ-15), and the Brief Illness Perception Questionnaire (BIPQ) measured health-related quality of life, psychological distress, somatic symptom severity, and illness perception respectively. Clinically significant improvements on the EPS-25 were identified using the Reliable Change Index. Patients were subsequently categorised as making a clinically significant improvement or not, and compared on all available demographic and clinical symptomology variables. Results: We observed a significant reduction on the EPS-25 (p=0.049) following Brief Augmented Psychodynamic Interpersonal Therapy for FNS. Change scores on the EPS-25 correlated positively with improvements on the mental health subscale of the SF-36 (r=0.634) and the CORE-10 (r=0.673). BIPQ scores were significantly lower (p=0.013) and SF-36 scores were significantly higher (p=0.020) post-therapy. 22% of patients made a clinically significant improvement on the EPS-25. However, we were unable to identify any demographic or clinical symptomology variables which differed significantly between patients who made a clinically significant improvement in emotion processing and those who did not. Conclusion: Emotion processing in patients with FNS improved following treatment with Brief Augmented Psychodynamic Interpersonal Therapy. This improvement was related to a reduction in psychological distress and improved mental health-related quality of life. Patients also perceived their symptoms as less threatening and experienced an improved health-related quality of life following intervention. Further work is required to establish characteristics which could identify patients who are particularly likely to improve in emotion processing with Brief Augmented Psychodynamic Interpersonal Therapy for FNS.